2012
DOI: 10.1007/s00216-012-5868-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a multi-residue method for the determination of several antibiotic groups in honey by LC-MS/MS

Abstract: The presented multi-method was developed for the confirmation of 37 antibiotic substances from the six antibiotic groups: macrolides, lincosamides, quinolones, tetracyclines, pleuromutilines and diamino-pyrimidine derivatives. All substances were analysed simultaneously in a single analytical run with the same procedure, including an extraction with buffer, a clean-up by solid-phase extraction, and the measurement by liquid chromatography tandem mass spectrometry in ESI+ mode. The method was validated on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Two lots of SPE cartridges and both new and old LC columns were included in validation testing. Samples were analysed immediately following extraction and after storage for 12 h. The method was validated in accordance with European Commission Decision 2002/657/EC and is an official method of German National Reference Laboratories (Bohm et al 2012).…”
Section: Multi-class Methodsmentioning
confidence: 99%
“…Two lots of SPE cartridges and both new and old LC columns were included in validation testing. Samples were analysed immediately following extraction and after storage for 12 h. The method was validated in accordance with European Commission Decision 2002/657/EC and is an official method of German National Reference Laboratories (Bohm et al 2012).…”
Section: Multi-class Methodsmentioning
confidence: 99%
“…However, the low volatility of some PAS and the presence of various polar groups in others require the use of an appropriate derivatization procedure to obtain more volatile products. In recent years, several methods based on liquid chromatography-mass spectrometry (Huang et al, 2006), tandem mass spectrometry (Ashwin et al, 2005;Bohm et al, 2012;Garrido Frenich et al, 2010;Martinez Vidal et al, 2009;Wang et al, 2014), mass time-of-flight mass spectrometry (Peters, Bolck, Rutgers, Stolker, & Nielen, 2009) and tandem quadrupole time-of-flight mass spectrometry detection (Deng et al, 2011) have been successfully used to determine PASs in eggs, honey and other food commodities with good sensitivity and selectivity. Recently, methodologies using ultrahigh-performance liquid chromatography and electrospray ionization quadrupole Orbitrap high-resolution mass spectrometry have been developed for the separation and detection of pesticides and veterinary drugs in honey (Gómez-Pérez et al, 2012) or baby food (Jia, Chu, Ling, Huang, & Chang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, analytes are extracted from theses matrices by liquid-liquid extraction, occasionally with the aid of solid-phase extraction (SPE) for cleanup purposes (Hao, Zhao, & Yang, 2007). The hydrophilic-lipophilic balanced sorbent Oasis HLB is the most widely used for extracting polar and nonpolar pharmaceutical compounds (Bohm, Stachel, & Gowik, 2012;Deng et al, 2011;Garrido Frenich, del Mar Aguilera-Luiz, Martínez Vidal, & Romero-González, 2010;Martinez Vidal et al, 2009;Sánchez-Brunete, Albero, Miguel, & Tadeo, 2005). Other sorbents such as silica (Courant et al, 2007(Courant et al, , 2008, Strata-X (Ashwin, Stead, Taylor, Startin, & Richmond, 2005), RP-C18 (Rejtharová & Rejthar, 2009) and molecularly imprinted polymers (Blasco & Picó, 2012;Rejtharová & Rejthar, 2009) have also been used for the SPE of PASs from eggs and honey.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported methodologies based on liquid chromatography couple to mass spectrometry in single or tandem mode (LC-MS and LC-MS/MS, respectively) to determine macrolides and lincosamides residues in milk [11][12][13][14] and muscle [15][16][17][18][19][20][21], and also in different matrices, such as honey [22,23], eggs [24], fish [25] and kidney [26,27]. These compounds are routinely included in multiresidue methodologies [14,16,19,[22][23][24][28][29][30][31], and there is minor publications of macrolides class only [32,33] or macrolides and lincosamides only [21]. For instance, Freitas et al use extraction with acetonitrile to analyze milk and bovine muscle to screening of several antibiotics, including four macrolides [34,35].…”
Section: Introductionmentioning
confidence: 99%